From isolation to application: a case study of arbuscular mycorrhizal fungi of the Arabian Peninsula - Mohamed N. Al-Yahya’ei; Janusz Błaszkowski; Hamood Al-Hashmi; Khaled Al-Farsi; Ismail Al-Rashdi; Annette Patzelt; Thomas Boller; Andres Wiemken; Sarah Symanczik (Symbiosis, 2022)
The vegetation in the Arabian Peninsula experiences drought, heat, soil salinity, and low fertility, mainly due to low phosphorus (P) availability. The beneficial mycorrhizal symbiosis between plants and arbuscular mycorrhizal fungi (AMF) is a key factor supporting plant growth under such environmental conditions. Therefore, AMF strains isolated from these soils might be useful as biotechnological tools for agriculture and revegetation practices in the region. Here we present a pioneering program to isolate, identify, and apply AMF isolated from rhizosphere soils of agricultural and natural habitats, namely date palm plantations and five native desert plants, respectively in the Southern Arabian Peninsula. We established taxonomically unique AMF species as single-spore cultures as part of an expanding collection of AMF strains adapted to arid ecosystems. Preliminary experiments were conducted to evaluate the abilities of these AMF strains to promote seedling growth of a main crop Phoenix dactylifera L. and a common plant Prosopis cineraria L. (Druce) in the Arabian Peninsula. The results showed that inoculation with certain AMF species enhanced the growth of both plants, highlighting the potential of these fungi as part of sustainable land use practices in this region.

Effects of two contrasted arbuscular mycorrhizal fungal isolates on nutrient uptake by Sorghum bicolor under drought - Sarah Symanczik; Moritz F. Lehmann; Andres Wiemken; Thomas Boller; Pierre-Emmanuel Courty (Mycorrhiza, 2018)

Phylogenetic, structural, and functional characterization of AMT3;1, an ammonium transporter induced by mycorrhization among model grasses - Sally Koegel; Delphine Mieulet; Sefer Baday; Odile Chatagnier; Moritz F. Lehmann; Andres Wiemken; Thomas Boller; Daniel Wipf; Simon Bernèche; Emmanuel Guiderdoni; Pierre-Emmanuel Courty (Mycorrhiza, 2017)

Options of partners improve carbon for phosphorus trade in the arbuscular mycorrhizal mutualism - Alicia Argüello; Michael J. O'Brien; Marcel G.A. van der Heijden; Andres Wiemken; Bernhard Schmid; Pascal A. Niklaus (Ecology Letters, 2016)
The mutualism between plants and arbuscular mycorrhizal fungi ( AMF ) is widespread and has persisted for over 400 million years. Although this mutualism depends on fair resource exchange between plants and fungi, inequality exists among partners despite mechanisms that regulate trade. Here, we use 33 P and 14 C isotopes and a split‐root system to test for preferential allocation and reciprocal rewards in the plant– AMF symbiosis by presenting a plant with two AMF that differ in cooperativeness. We found that plants received more 33 P from less cooperative AMF in the presence of another AMF species. This increase in 33 P resulted in a reduced 14 C cost per unit of 33 P from less cooperative AMF when alternative options were available. Our results indicate that AMF diversity promotes cooperation between plants and AMF , which may be an important mechanism maintaining the evolutionary persistence of and diversity within the plant– AMF mutualism.

Impact of water regimes on an experimental community of four desert arbuscular mycorrhizal fungal (AMF) species, as affected by the introduction of a non-native AMF species - Sarah Symanczik; Pierre-Emmanuel Courty; Thomas Boller; Andres Wiemken; Mohamed N. Al-Yahya’ei (Mycorrhiza, 2015)

Unique arbuscular mycorrhizal fungal communities uncovered in date palm plantations and surrounding desert habitats of Southern Arabia - Mohamed N. Al-Yahya’ei; Fritz Oehl; Marta Vallino; Erica Lumini; Dirk Redecker; Andres Wiemken; Paola Bonfante (Mycorrhiza, 2011)

Protein phosphatase activity and sucrose-mediated induction of fructan synthesis in wheat - Giselle M. A. Martínez-Noël; Jorge A. Tognetti; Graciela L. Salerno; Andres Wiemken; Horacio G. Pontis (Planta, 2009)

Impact of antifungals producing rhizobacteria on the performance of Vigna radiata in the presence of arbuscular mycorrhizal fungi - Deepti Dwivedi; Bhavdish N. Johri; Kurt Ineichen; Victor Wray; Andres Wiemken (Mycorrhiza, 2009)

Promiscuous arbuscular mycorrhizal symbiosis of yam (Dioscorea spp.), a key staple crop in West Africa - Atti Tchabi; Stefanie Burger; Danny Coyne; Fabien Hountondji; Louis Lawouin; Andres Wiemken; Fritz Oehl (Mycorrhiza, 2009)

An acceptor-substrate binding site determining glycosyl transfer emerges from mutant analysis of a plant vacuolar invertase and a fructosyltransferase - Denise Altenbach; Enrique Rudiño-Pinera; Clarita Olvera; Thomas Boller; Andres Wiemken; Tita Ritsema (Plant Molecular Biology, 2009)

Arbuscular mycorrhizal fungal communities in sub-Saharan Savannas of Benin, West Africa, as affected by agricultural land use intensity and ecological zone - Atti Tchabi; Danny Coyne; Fabien Hountondji; Louis Lawouin; Andres Wiemken; Fritz Oehl (Mycorrhiza, 2008)

Medicago truncatula shows distinct patterns of mycorrhiza-related gene expression after inoculation with three different arbuscular mycorrhizal fungi - Nadja Feddermann; Thomas Boller; Peter Salzer; Sara Elfstrand; Andres Wiemken; Malin Elfstrand (Planta, 2008)

The cultivation bias: different communities of arbuscular mycorrhizal fungi detected in roots from the field, from bait plants transplanted to the field, and from a greenhouse trap experiment - Zuzana Sýkorová; Kurt Ineichen; Andres Wiemken; Dirk Redecker (Mycorrhiza, 2007)

Calcium is essential for fructan synthesis induction mediated by sucrose in wheat - Giselle Martínez-Noël; Jorge Tognetti; Vinay Nagaraj; Andres Wiemken; Horacio Pontis (Planta, 2006)

Communities of arbuscular mycorrhizal fungi in arable soils are not necessarily low in diversity - ISABELLE HIJRI; ZUZANA SÝKOROVÁ; FRITZ OEHL; KURT INEICHEN; PAUL MÄDER; ANDRES WIEMKEN; DIRK REDECKER (Molecular Ecology, 2006)
Communities of arbuscular mycorrhizal fungi (AMF) in five agricultural field sites of different management intensities were studied. Variable regions of the ribosomal RNA genes were used to detect and identify AMF directly within colonized roots. Roots from a continuous maize monoculture showed low AMF diversity, in agreement with previous reports on molecular diversity of AMF in agricultural soils. In contrast, a substantially higher diversity of AMF was found throughout the long term ‘DOK’ field experiment, where organic and conventional agricultural practices have been compared side by side since 1978. In this experiment, a 7‐year crop rotation is performed under lower levels of inorganic fertilizer input and chemical pest control. These results are in good agreement with analyses of the spore community previously conducted in these field sites. In a third site, an organically managed leek field with soil of very high phosphate content reflecting the highly intensive conventional field history and intensive tillage, we detected a low‐diversity community comparable to the maize monoculture. In addition to fungi from Glomus group A, which have previously been reported to dominate arable soils, we regularly found members of the genera Scutellospora , Paraglomus and Acaulospora. The genus Acaulospora was shown to occur more frequently early in the growing season, suggesting that the life history strategy of AMF may influence the active community at a given time. These data show that the diversity of AMF is not always low in arable soils. Furthermore, low‐input agriculture involving crop rotation may provide better conditions to preserve AMF diversity, by preventing the selection for the few AMF taxa tolerating high nutrient levels.

Sinorhizobium meliloti-induced chitinase gene expression in Medicago truncatula ecotype R108-1: a comparison between symbiosis-specific classV and defence-related classIV chitinases - Peter Salzer; Nadja Feddermann; Andres Wiemken; Thomas Boller; Christian Staehelin (Planta, 2004)

Impact of long-term conventional and organic farming on the diversity of arbuscular mycorrhizal fungi - Fritz Oehl; Ewald Sieverding; Paul Mder; David Dubois; Kurt Ineichen; Thomas Boller; Andres Wiemken (Oecologia, 2004)

Hyphal in vitro growth of the arbuscular mycorrhizal fungus Glomus mosseae is affected by chitinase but not by β-1,3-glucanase - Horst Vierheilig; Monica Alt-Hug; Andres Wiemken; Thomas Boller (Mycorrhiza, 2001)

Arbuscular mycorrhizae in a long-term field trial comparing low-input (organic, biological) and high-input (conventional) farming systems in a crop rotation - P. Mäder; Stephan Edenhofer; Thomas Boller; Andres Wiemken; Urs Niggli (Biology and Fertility of Soils, 2000)

Trehalose in yeast, stress protectant rather than reserve carbohydrate - Andres Wiemken (Antonie van Leeuwenhoek, 1990)

Localization of trehalase in vacuoles and of trehalose in the cytosol of yeast (Saccharomyces cerevisiae) - Felix Keller; Maja Schellenberg; Andres Wiemken (Archives of Microbiology, 1982)

Asymmetric distribution of Concanavalin A binding sites on yeast plasmalemma and vacuolar membrane - Thomas Boller; Mathias Drr; Andres Wiemken (Archives of Microbiology, 1976)

Polybase induced lysis of yeast spheroplasts - Mathias Drr; Thomas Boller; Andres Wiemken (Archives of Microbiology, 1975)

Characterization of amino acid pools in the vacuolar compartment of Saccharomyces cerevisiae - Andres Wiemken; Mathias Drr (Archives of Microbiology, 1974)